Application of Social Media Marketing in Increasing The Competitiveness Of Syrup Business on CV. Nuh Aurora Makassar - Citra, Widya; Aslinda, Aslinda; Baharuddin, Aris (Pinisi Business Administration Review, 2025)
Application of Social Media Marketing in Increasing the Competitiveness of Syrup Businesses at CV. Nuh Aurora Makassar is one way to expand marketing coverage. Social media marketing is very important in increasing sales and competitiveness. The problem that then arises is how to apply social media marketing and the determinant factors in increasing competitiveness. To achieve this goal, data collection techniques are used through observation, interviews, and documentation. Data is processed using a descriptive qualitative approach. This study took 2 (person) respondents who were owners and employees of Aurora Passion Fruit Syrup. Source of data in this research is primary data. The interview technique was carried out in a structured manner using interview guidelines. The results of this study indicate that the application of social media marketing uses a website, namely Google My Business, then uses social media, namely Instagram, and Facebook ads. From this application, auora passion fruit syrup can reach more consumers and markets so that it can increase its competitiveness. The determinant factors that influence the application of social media marketing are supporting factors consisting of product quality and social media used. The inhibiting factors are negative reviews or comments that cannot be controlled, and human resources that are lacking in social media and marketing